How can outdoor sports protect themselves against climate change-related health risks?: A prevention model based on an expert Delphi study - Schneider, Sven; Niederberger, Marlen; Kurowski, Luke; Bade, Luisa (Journal of science and medicine in sport, 2024)
Objectives - To systematically develop an adaptation model to reduce climate change-related health risks for outdoor athletes. - Design - Delphi Method study. - Methods - A classic asynchronous Delphi study was conducted with a total of three survey rounds. 24 experts from the eight largest outdoor sport associations by membership in the German Olympic Sports Confederation were included as well as 24 medical experts with expertise in sport medicine, internal medicine, allergology, dermatology, infectiology, or toxicology. Based on open-ended questions, panelists were asked to consider prevention measures for sport organizations and clubs. Free text responses were analyzed by qualitative content analysis according to Mayring. - Results - Experts recommended establishing the following eight fields of prevention measures: technical and structural measures; organizational measures; personalized measures; basic, advanced, and continuing education; concepts of action, warning concepts, and financial concepts; cooperation and coordination; campaigns; and evaluation measures. - Conclusions - The pyramid model presented in this study systematizes possible sport-specific adaptation measures on climate change by empirical aggregation of knowledge from scientists, sport organizations, clubs, trainers, and professional athletes. To assess the effectiveness of these prevention measures, sport organizations may incorporate them not only into broader operations but also everyday training routines.
Online verfügbar: 11 November 2023
Gesehen am 11.07.2024